An Experiential Approach to Sport for Youth Development. (September 2017) - Newman, Tarkington J.; Alvarez, M. Antonio G.; Kim, Melissa
Experiential learning has been used to inform programming and practices in a wide variety of contexts such as adventure therapy and outdoor education. Furthermore, experiential learning has been used to explain the learning process of individuals, groups, and teams. Its relationship with the context of youth sport, however, has yet to be fully explored. Within youth sport, especially sport-based positive youth development (PYD), experiential learning can be utilized to help guide programming and practices of the youth sport leader (YSL). The integration of sport-based PYD and experiential learning is important, as research has indicated that YSLs lack intentionality as they aim to facilitate sport toward youth development. To highlight the potential integration of sport-based PYD and experiential learning, one previously developed model is identified. Moreover, the utilization of experiential learning within sport-based PYD is discussed to help illuminate the potential impact of experiential learning in both research and practice.